2015
DOI: 10.1002/cncr.29652
|View full text |Cite
|
Sign up to set email alerts
|

Addition of radiotherapy to adjuvant chemotherapy is associated with improved overall survival in resected pancreatic adenocarcinoma: An analysis of the National Cancer Data Base

Abstract: BACKGROUND:The optimal treatment for resected pancreatic cancer is controversial because direct comparisons of adjuvant chemotherapy (CT) alone and chemotherapy and radiotherapy (CRT) are limited. This study assessed outcomes of CT versus CRT in a national cohort to provide a modern estimate of comparative effectiveness. METHODS: Patients with pT1-3N0-1M0 pancreatic adenocarcinoma after pancreatectomy were identified in the National Cancer Data Base. Overall survival (OS) was compared for CT and CRT groups wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
61
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 30 publications
3
61
1
Order By: Relevance
“…[19][20][21][22][23] A retrospective study from the Mayo Clinic that included 472 patients investigated outcomes after surgery alone versus surgery plus adjuvant CRT. OS was better in patients who received adjuvant CRT (median OS, 25.2 vs. 19.2 months, P = 0.001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[19][20][21][22][23] A retrospective study from the Mayo Clinic that included 472 patients investigated outcomes after surgery alone versus surgery plus adjuvant CRT. OS was better in patients who received adjuvant CRT (median OS, 25.2 vs. 19.2 months, P = 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Adjuvant CRT was independently associated with improved OS compared with adjuvant chemotherapy (median 22.3 vs. 20.0 months, P = 0.001). [23] The benefit of adjuvant RT with modern techniques is still controversial and the subgroup that can benefit most from this approach is not well defined. A well-designed randomized controlled study with modern techniques will be necessary to confirm the efficacy of adjuvant CRT in this population.…”
Section: Discussionmentioning
confidence: 99%
“…Several contemporary retrospective studies suggest that there is a survival benefit[36-39]. Rutter et al[36] reviewed the national cancer database in the United States and identified 6165 patients from 1998 to 2009 who were treated with adjuvant chemotherapy or chemoradiotherapy. The mean radiotherapy dose received was 50.4 Gy, which was higher than the doses used in older prospective studies.…”
Section: Adjuvant Chemoradiotherapymentioning
confidence: 99%
“…Current data suggests that a consolidative approach after completing systemic treatment options and careful restaging might be reasonable. A positive role of post-operative radiotherapy was confirmed by a large retrospective analysis [13] which identified radiotherapy in addition to adjuvant chemotherapy as a favorable prognostic indicator for survival.…”
Section: Introductionmentioning
confidence: 99%